Communicability problems on MOOCs: a study around metacommunication - do Rêgo, Beatriz B.; Garrido, Filipe A.; Rosa, Jean C. S.; Matos, Ecivaldo S. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
The MOOCs emerged as instruments for the democratization of education through free online courses. However, MOOCs have a high dropout rate among students. In this sense, this paper presents some results on whether communicability problems are related to the general causes of dropout in MOOC courses. To achieve this objective, the Semiotic Inspection Method was applied in the Coursera and EDx MOOC platforms. From the results, it was inferred that communicability problems are associated with some of the general causes that lead to the abandonment or withdrawal of students in MOOCs.